2006
DOI: 10.1158/1078-0432.ccr-06-0825
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 20q13.2 Gain May Predict Intravesical Recurrence after Nephroureterectomy in Upper Urinary Tract Urothelial Tumors

Abstract: Purpose: Amplification or gain of copy number of chromosome 20q13.2 has been implicated as a causal factor for chromosome instability.We investigated the impact of chromosomal instability and its causative molecular markers, 20q13.2 gain and centrosome amplification, on patient outcome in upper urinary tract transitional cell carcinoma (UUT-TCC). Experimental Design: The number of centrosomes was assessed by immunohistochemistry. Numerical aberrations of chromosomes 7, 9, and 17 that allowed the estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…33 The 20q13 chromosomal region, however, is very gene rich, and there may be other candidate genes explaining the relation to metastasis. Gains and amplifications of the 20q13.2 region have been correlated with lymph node status in gastric cancer, 34 with recurrence in urothelial tumors, 35 and with tumor progression in colorectal carcinoma. 36 This preliminary finding needs to be confirmed in studies with a larger number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…33 The 20q13 chromosomal region, however, is very gene rich, and there may be other candidate genes explaining the relation to metastasis. Gains and amplifications of the 20q13.2 region have been correlated with lymph node status in gastric cancer, 34 with recurrence in urothelial tumors, 35 and with tumor progression in colorectal carcinoma. 36 This preliminary finding needs to be confirmed in studies with a larger number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…aCGH analysis) and CIN (in FISH analysis) than those without it, and this association was more significant than that between tumor grade and DCNAs/CIN. Recent studies have reported that CA is closely related to the phenotypes of high tumor grade and CIN in human malignancies [12,13] including urothelial carcinomas of the bladder [15] and upper urinary tract [14]. It was also reported that, in an aCGH analysis of urothelial carcinomas, high-grade tumors contained DNA copy number gains and amplifications considerably more frequently than low-grade tumors [23].…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively reviewed the records of these patients. Follow-up included regular clinical examination as described previously [14,16]. Tumor recurrence was defined as a new tumor detected either by regular follow-up cystoscopy for local recurrence or by radiographic imaging for distant metastasis.…”
Section: Patients and Tissue Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has suggested that centrosome amplification, which leads to the formation of multipolar spindles and unequal segregation of chromosomes, is both a common and major factor for chromosomal instability (CIN) [1] [2] in several human malignancies [3][4][5]. Previous studies have reported that centrosome amplification is closely related not only to the tumor grade and DNA ploidy but also to CIN in bladder cancer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%